Utilization of Bentonite and Hybrid UF-RO in Treatment of Pulp Industry Wastewater - Subriyer Nasir; Silvester Chrisya Andira; Vera Dona (Jurnal Inovasi Teknologi, 2020)
The purpose of this research is to investigate the performance of bentonite,hybrid of ultra-filtration and reverse osmosis (UF-RO) in improving the quality of liquid waste produced by pulp industry. The parameter used in this research is pH, turbidity, and Chemical Oxygen Demand (COD). The variable examined is operating time and feed water flow rate. The results show that the hybrid of UF-RO is able to produce permeates with optimum pH of 7,23 at 60 minutes operating time and reduce the turbidity almost 99% of the COD to 18 mg. L-1. It is suggested that the Bentonite and hybrid of UF/RO can be applied in the treatment of pulp and paper industries.